Computational Study of (E)-4-hydroxy-3-(phenylamino)pent-3-en-2-one as A Novel Organic Corrosion Inhibitors - Aseer shakir Ajel (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
This study investigates the corrosion inhibition potential of a newly synthesized organic compound, (E)-4-hydroxy-3-(phenylamino)pent-3-en-2-one (LASA3), using computational chemistry approaches. Density Functional Theory (DFT) calculations were performed at the B3LYP/6-31G(d) level of theory with the Gaussian09 software package to evaluate several key quantum chemical parameters. These parameters include total energy, the energies of the highest occupied molecular orbital (EHOMO) and lowest unoccupied molecular orbital (ELUMO), the energy gap (ΔEgap), dipole moment, chemical hardness, softness (σ), and the number of electrons transferred (ΔN). The computational results reveal that LASA3 exhibits a higher EHOMO value and a smaller ΔEgap compared to its precursor molecules, referred to as S.M.1 and S.M.2. A higher EHOMO value suggests that LASA3 has a greater electron-donating ability, which enhances its interaction with the metal surface. Likewise, the reduced ΔEgap indicates greater chemical reactivity and a higher likelihood of forming stable coordination bonds with iron atoms on the carbon steel surface. Electrostatic potential (ESP) map analysis further supports these findings by highlighting the distribution of electron density within the LASA3 molecule. The ESP maps show significant electron-rich regions localized around nitrogen and oxygen atoms, which are potential active sites for adsorption onto the steel surface. This adsorption process plays a crucial role in blocking active corrosion sites and reducing the rate of metal degradation. In conclusion, the theoretical analysis confirms that LASA3 has superior electronic properties for corrosion inhibition compared to its starting materials, S.M.1 and S.M.2. Its ability to donate electrons, favorable dipole characteristics, and strategically located electron-rich sites make it a promising candidate for further experimental evaluation as an efficient corrosion inhibitor for carbon steel applications.